Participation of Parents and Community Leaders in the Implementation of Early Childhood Education Kotenwalang in Tanjung Bunga District, East Flores Regency - Maria Katharina Sekosi; Lukas Maria Boleng; Credo G. Betty (Early Childhood Education Development and Studies (ECEDS), 2021)
This research aims to describe the form of participation of parents and community leaders in the performance of PAUD Kotenwalang at Latonliwo Village, Tanjung Bunga District, East Flores Regency. The subjects of this study were the principal, teachers and student parents at PAUD Kotenwalang; as well as residents and community leaders at Latonliwo Village. Data were collected by interviews and observations during the study. The results showed that the forms of parent participation in PAUD Kotenwalang are work partners, liaison of PAUD with the home, supporter of PAUD, involved as volunteers, and supporter of educational goals. While the form of participation of community is as motivator, contributor of resources, and improving the quality of PAUD. The interesting thing found in this study was the highly involvement of parents and community leaders in the performance of PAUD Kotenwalang.